The Interaction of Authority Between Notaries and Land Deed Officials (PPAT) in Land Transactions: An Analysis of Legal Certainty and Normative Solutions - Lado, Dedy Alexander; Rini, Indrati (Dinasti Research, 2025)
This study aims to analyze the interaction of authority between Notaries and Land Deed Officials (PPAT) in the execution of land transaction deeds, emphasizing the aspect of legal certainty and the accountability of public officials. The issue arises due to overlapping authorities in practice, particularly when a Notary simultaneously holds the position of a PPAT in transferring land rights. This dual function often results in differing interpretations regarding the validity of deeds, the legitimacy of the officiating authority, and the resulting legal consequences for the parties involved. In addition, the Indonesian legal system has not yet firmly delineated the jurisdictional boundaries between the Notary and PPAT offices, creating potential uncertainty in the execution of authentic deeds.This research employs a normative juridical method with a combination of statute, conceptual, and case approaches. The statute approach examines the harmonization between the Law on Notary Office and the Regulation on PPAT Office. The conceptual approach interprets legal theories of competence, public responsibility, and legal certainty, while the case approach analyzes five key Supreme Court decisions that deal with the validity of deeds and overreach of authority.The results reveal an urgent need for legal harmonization and the establishment of concrete implementation guidelines that clarify the separation of authority between Notaries and PPATs. Furthermore, the study proposes the strengthening of professional supervision and accountability to prevent authority conflicts and to ensure a consistent standard of legal protection for the public.